Change in Chemical Composition of Simmental Crossbred Cattle Milk Improved its Physicochemical, Nutritional, and Processed Properties. Issue 6 (27th May 2019) - Li, Xin; Ma, Xin; Xiao, Na; Long, Wei; Wu, Yong; Tong, Ping; Chen, Hongbing
Abstract : Abstract: This study aimed to evaluate a new milk resource from Simmental crossbred cattle, which could be an alternative raw milk for dairy products. In the experiment, physicochemical characterization of raw milk was evaluated according to the Standards. In addition, Simmental crossbred cattle milk (SHCM) samples had the higher contents of total amino acid than those of Chinese Holstein cow milk (HCM) samples, especially for Leu, Lys, Met, and Phe. We also observed the contents of protein, fat, and lactose in SHCM samples changed during 12 months, where in milk fat content was mostly affected by the season, followed by the lactose and protein contents. Moreover, texture profile analysis showed that yoghurt made from SHCM had stronger structures, which especially reflected in hardness and chewiness. The G' of yoghurt made from SHCM during storage time was always higher than that made from HCM, indicating that SHCM yoghurt showed higher apparent viscosity values. Logically, the milk from Simmental crossbred cattle has desirable physicochemical characteristics and nutritional value, which could be a new better resource of dairy products. Practical Application: Compared with Chinese Holstein cattle, Simmental crossbred cattle have strong resistance to moist weather and better performance in disease resistance, which are particularly important for lactating cows persisting in south of China. We evaluated the nutritional values of SHCM and HCM, and compared the seasonal variation on chemical composition of SHCM sample. All the data could be used to produce different dairy products using raw milk from different seasons. In addition, textural properties of yoghurt made from two milks were also determined, and we suggested that SHCM could be used as a new resource candidate for developing dairy product in the future.